2015
DOI: 10.1057/jibs.2015.14
|View full text |Cite
|
Sign up to set email alerts
|

Global delivery models: The role of talent, speed and time zones in the global outsourcing industry

Abstract: Abstract:We investigate antecedents and contingencies of location configurations supporting global delivery models (GDMs) in global outsourcing. GDMs are a new form of IT-enabled client-specific investment promoting services provision integration with clients by exploiting client proximity and time-zone spread allowing for 24/7 service delivery and access to resources. Based on comprehensive data we show that providers are likely to establish GDM configurations when clients value access to globally distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 92 publications
1
64
2
Order By: Relevance
“…Bunyaratavej et al 2007;Gerbl et al 2015;Mukherjee et al 2013;Schmeisser 2013), governance modes (Kedia and Mukherjee 2007;Luo et al 2013), geographical configurations (Manning et al 2015), and organizational (re-)design (Jensen et al 2013;Lampel and Bhalla 2011;Schmeisser 2013). With regard to motivations for advanced task offshoring, a large body of research across academic disciplines has identified factors that determine the cost-benefits ratio of advanced task offshoring for an organization.…”
Section: Advanced Task Offshoringmentioning
confidence: 99%
“…Bunyaratavej et al 2007;Gerbl et al 2015;Mukherjee et al 2013;Schmeisser 2013), governance modes (Kedia and Mukherjee 2007;Luo et al 2013), geographical configurations (Manning et al 2015), and organizational (re-)design (Jensen et al 2013;Lampel and Bhalla 2011;Schmeisser 2013). With regard to motivations for advanced task offshoring, a large body of research across academic disciplines has identified factors that determine the cost-benefits ratio of advanced task offshoring for an organization.…”
Section: Advanced Task Offshoringmentioning
confidence: 99%
“…(e.g., Argyres, 1999;Kumar et al, 2009;Manning, Larsen, & Bharati, 2015;Rangan & Sengul, 2009). Without ICT-enabled interfacing, in many cases process fragmentation would be nor technically feasible nor economically viable.…”
Section: The Enabling Role Of Ictsmentioning
confidence: 99%
“…With ICT-enabled interfacing, firms can fragment processes across multiple service production units, whether internal or outsourced, so that no one center can reconstruct the entire knowledge basis of a service. The use of modern ICT would then contribute to the development of the necessary integration capabilities (e.g., for firms to coordinate and control interdependent process fragments (Rangan & Sengul, 2009, see also Ceci & Prencipe, 2013;Kumar et al, 2009;Manning et al, 2015), and hence leverage the added value of dispersed service production units while limiting the extra cost of organizational complexity.…”
Section: The Enabling Role Of Ictsmentioning
confidence: 99%
“…In particular, we discuss how certain industry conditions may lower the need to scale up hybrids to make them competitive and impactful and instead allow heterogeneous populations of smaller‐scale hybrids to emerge. Third , we extend prior research on global business services (e.g., Manning et al, ) by discussing impact sourcing as a new strategy of local adaptation and differentiation in a highly competitive market.…”
Section: Introductionmentioning
confidence: 99%